Bovine Meniscus Middle Zone Tissue: Measurement of Collagen Fibril Behavior During Compression - Sizeland KH (Dove Medical Press, 2020)
Katie H Sizeland,1 Hannah C Wells,2 Nigel M Kirby,3 Adrian Hawley,3 Stephen T Mudie,3 Tim M Ryan,3 Richard G Haverkamp2 1Human Health, ANSTO, Lucas Heights, Sydney, NSW 2234, Australia; 2School of Food and Advanced Technology, Massey University, Palmerston North 4472, New Zealand; 3SAXS/WAXS Beamline, Australian Synchrotron, ANSTO, Clayton, Melbourne, VIC 3168, AustraliaCorrespondence: Richard G HaverkampSchool of Food and Advanced Technology, Massey University, Private Bag 1112, Palmerston North 4472, New ZealandTel +64 6 356 9099Email r.haverkamp@massey.ac.nzBackground: Type I collagen is the major component of the extracellular matrix of the knee’s meniscus and plays a central role in that joint’s biomechanical properties. Repair and reconstruction of tissue damage often requires a scaffold to assist the body to rebuild. The middle zone of bovine meniscus is a material that may be useful for the preparation of extracellular matrix scaffolds.Methods: Here, synchrotron-based small-angle X-ray scattering (SAXS) patterns of bovine meniscus were collected during unconfined compression. Collagen fibril orientation, D-spacing, compression distance and force were measured.Results: The collagen fibrils in middle zone meniscal fibrocartilage become more highly oriented perpendicular to the direction of compression. The D-spacing also increases, from 65.0 to 66.3 nm with compression up to 0.43 MPa, representing a 1.8% elongation of collagen fibrils perpendicular to the compression.Conclusion: The elasticity of the collagen fibrils under tension along their length when the meniscus is compressed, therefore, contributes to the overall elastic response of the meniscus only under loads that exceed those likely to be experienced physiologically.Keywords: collagen, meniscus, compression, SAXS, scaffold